Gender-specific associations of genetic variants with metabolic syndrome components in the Tunisian population. (1st October 2016) - Elouej, Sahar; Rejeb, Insaf; Attaoua, Redha; Nagara, Majdi; Sallem, Om Kalthoum; Kamoun, Ines; Chargui, Mariem; Jamoussi, Henda; Turki, Zinet; Abid, Abdelmajid; Ben Slama, Claude; Bahri, Sonia; et al.
ABSTRACT: Aim of the study: Recent genome-wide association studies (GWASs) have identified many genetic variants associated with metabolic syndrome (MetS). However, their contribution to MetS in ethnic groups in Tunisia is largely unexplored. In this study, we aim to examine the associations of related loci with a risk of metabolic syndrome in a sample of Tunisians.Materials and methods: Overall seven polymorphisms rs7265718, rs10401969, rs762861, rs12310367, rs1562398, rs2059807, rs4420638 located at C20orf152, CILP2, LRPAP1, ZNF664, KLF14, INSR, APOE, respectively, were analyzed in 356 samples from the Tunisian population. Anthropometric and biochemical parameters were assessed. Metabolic syndrome was defined according to the International Diabetes Federation (IDF).Results: We find that LRPAP1 -rs762861 C allele increases susceptibility to MetS (OR = 1.39, 95% CI = 0.99–1.95, p = 0.041). Separate analysis in men and women revealed the association of rs762861 among females (OR = 1.6, 95% CI = 1.057–2.41, p = 0.021), but not among males (OR = 0.953, 95% CI = 0.51–1.78, p = 0.882). ZNF664 -rs12310367 was also found to be associated with body mass index (BMI) in women ( p = 0.01) and not in men ( p = 0.18). KLF14- rs1562398 was significantly correlated with impaired fasting glucose ( p = 0.004) only in men.Conclusions: Our results reveal new candidate genes for MetS in the Tunisian population and suggest that the genetic basis of this syndrome is gender dependent. Further studies are necessary to understand why these associations differ between males and females.